2017
DOI: 10.1098/rsos.160773
|View full text |Cite
|
Sign up to set email alerts
|

Historical gene flow constraints in a northeastern Atlantic fish: phylogeography of the ballan wrasseLabrus bergyltaacross its distribution range

Abstract: The distribution and demographic patterns of marine organisms in the north Atlantic were largely shaped by climatic changes during the Pleistocene, when recurrent glacial maxima forced them to move south or to survive in northern peri-glacial refugia. These patterns were also influenced by biological and ecological factors intrinsic to each species, namely their dispersion ability. The ballan wrasse (Labrus bergylta), the largest labrid fish along Europe's continental margins, is a target for fisheries and aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 78 publications
5
23
0
Order By: Relevance
“…This pattern of pre-LGM expansion has also been reported in a number of previous studies for a variety of marine taxa (e.g. Hoarau et al, 2007;Marko et al, 2010;Ni et al, 2014;Almada et al, 2017).…”
Section: Demographic Historysupporting
confidence: 85%
“…This pattern of pre-LGM expansion has also been reported in a number of previous studies for a variety of marine taxa (e.g. Hoarau et al, 2007;Marko et al, 2010;Ni et al, 2014;Almada et al, 2017).…”
Section: Demographic Historysupporting
confidence: 85%
“…These two morphotypes differs in life history traits such as growth, maturation and mortality rates [53,54] and a taxonomic reevaluation of the species has been proposed [55]. To date, knowledge of genetic population structure of ballan wrasse in Norway is limited to a couple of studies analysing mitochondrial DNA polymorphism on a few individuals from the southern coast [56,57], which makes it difficult to draw conclusions about the impact of the fishery and fish translocations on the genetic diversity.…”
Section: Ballan Wrasse Labrus Bergyltamentioning
confidence: 99%
“…Such population history of step-wise colonization would explain the observed phylogeny for goldsinny wrasse (see also e.g. Gysels et al 2015;Almada et al 2017). In a recent study, Mattingsdal and colleagues (2019) showed that the current-day population structure of corkwing wrasse in Scandinavia characterized by a substantial division between western and southern Scandinavia can mainly be explained with past demographic events followed by reproductive isolation and genetic drift.…”
Section: Discussionmentioning
confidence: 95%
“…Thus far, the best-studied of these species is the corkwing wrasse which displays clear population subdivisions on different geographic scales (Robalo et al 2012;Knutsen et al 2013;Blanco Gonzalez et al 2016;Mattingsdal et al 2019). Genetic studies of ballan wrasse have so far concentrated on investigation of population structure on larger geographic scales (D'Arcy et al 2013;Almada et al 2017), and on genetic divergence of different morphotypes (Quintela et al2016;Almada et al 2016). An early genetic study of goldsinny wrasse with allozyme markers showed significant differences between the southern and mid-Norway (Sundt & Jørstad 1998).…”
Section: Introductionmentioning
confidence: 99%